Hubungan Antara Pola Asuh Permisif dengan Empati Siswa Kelas VIII Di Smp Yappa Depok - Nur Khalida Al Zhahira; Reni Sinta Dewi; Ikhwan Hamdani (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2026)
Empathy, as the ability to understand and feel what others are experiencing, is an important aspect of students’ social and emotional development. Empathy can be shaped by parenting styles at home, but it can also be negatively affected, one of which is through permissive parenting. Permissive parenting is characterized by granting children broad freedom without sufficient supervision or discipline, and often indulging them by giving in to their demands. This study aims to determine the relationship between permissive parenting and the empathy of eighth-grade students at SMP Yappa Depok. The research method used is quantitative correlational, with data collected through questionnaires administered to a number of students. The research findings show that: (1) There are 59 eighth-grade students, or 64.1%, who experience permissive parenting at a moderate level; (2) A total of 64 students, or 69.6%, have empathy levels categorized as moderate; (3) Statistical hypothesis testing using Pearson Product-Moment correlation through SPSS version 26.0 shows that the Sig. (2-tailed) value is 0.000 < 0.05. It can be concluded that the alternative hypothesis (Ha) is accepted, indicating a significant relationship between permissive parenting and the empathy of eighth-grade students at SMP Yappa Depok.